Comparison of Polyjet Printing and Silicon Moulding as Rapid Plastic Moulding Solution - Singh, Rupinder (Universiti Malaysia Pahang, 2012)
The aim of the present investigation is to compare two rapid molding (RM) solutions, namely polyjet printing (PP) and silicon molding (SM), for the manufacture of plastic components. The comparison has been made on the basis of dimensional accuracy (as per IT grades), mechanical properties (namely surface hardness, surface roughness) and production cost. The comparison of the experimental results will serve as a yard stick for the further selection of processes for industrial applications.